2012
DOI: 10.1177/0963721412448651
|View full text |Cite
|
Sign up to set email alerts
|

Mood Regulation in Real Time

Abstract: Mechanisms have been proposed to underlie differences between younger and older adults in real-time mood regulation, but these mechanisms have not yet been shown to predict mood outcomes. One such mechanism is age-related positivity effects in attention and memory. In this paper, I take one form of this possible mechanism –positive looking patterns – and consider whether 1) older adults prefer positive looking, and 2) positive looking helps older adults regulate their mood in real-time. Evidence is more consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 34 publications
4
46
2
Order By: Relevance
“…Thus, positive looking may be generally preferred by older adults, but may only help a subset of older adults to regulate their mood. In contrast, we have found that younger adults’ moods tend to benefit from looking more at negative stimuli (Isaacowitz, 2012). …”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Thus, positive looking may be generally preferred by older adults, but may only help a subset of older adults to regulate their mood. In contrast, we have found that younger adults’ moods tend to benefit from looking more at negative stimuli (Isaacowitz, 2012). …”
mentioning
confidence: 62%
“…This corresponds to the emotion regulation strategy of attentional deployment, in which a person directs attention toward or away from an emotion-eliciting stimulus (Gross, 1998). Consistent with age-related positivity effects, numerous studies have found age differences in preferences, such that older adults look less at negative and more at positive stimuli (see Isaacowitz, 2012; Nikitin & Freund, 2011). …”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, by investigating mood effects in addition to attentional ones, we can also answer questions about potential age differences (and similarities) in the relationship between looking and mood regulation in a way that has not previously been done in midlife (Isaacowitz, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, SAVI posits that older adults shift toward strategies that allow them to regulate before a full-blown emotional response has unfolded, rather than strategies aimed at reducing existing negative emotions (Charles, 2010). For example, older adults shift their attention towards positive and away from negative emotional content (Reed, Chan & Mikels, 2014), which is associated with better emotional outcomes (see Isaacowitz, 2012 for a review).…”
Section: Emotion Regulation Across Adulthoodmentioning
confidence: 99%